Pengaruh Harga dan Kelengkapan Produk terhadap Minat Belanja di Mentari Swalayan dimana Kemudahan Belanja di Alfamart menjadi Variabel Moderating - Rusdawati, Rusdawati; Andriyati, Yuli (Universitas Darwan Ali, 2021)
This study was purposed to determine the effect of price and product completeness on shopping interest in Mentari Swalayan with the ease of shopping as a moderating variable. What is presented as a population is all customers who have shopped at Mentari Swalayan and Alfamart. The sampling method used was convenience sampling, in which the total amount of respondents was 112. The research instrument is a questionnaire using a Likert scale to collect data about price and product completeness variables and purchase desire, as well as the ease of shopping as a moderating using the HRA (Hierarchical Regression Analysis) method. The results of this study showed that price and product completeness partially and simultaneously have a positive significant effect on purchase intention. According to the result of data analysis, the ease of shopping does not moderate the effect of price and product completeness on shopping interest.